PENGARUH PENGAWASAN TERHADAP EFEKTIVITAS KEBIJAKAN PERATURAN BUPATI NO 63 TAHUN 2018 TENTANG SISTEM LAYANAN DAN RUJUKAN TERPADU (SLRT) DI DINAS SOSIAL KABUPATEN SUMEDANG - Fitrianingsih, Desi (LPPM UNSAP & FISIP UNSAP, 2025)
The purpose of this study was to determine Supervision and Effectiveness, to determine the relationship between Supervision and Effectiveness and to determine the magnitude of the influence of Supervision on Effectiveness in the Sumedang Regency Social Service. This study uses a descriptive analysis method with a quantitative approach and the type of statistics used is descriptive statistics with a non-probability sampling technique with a saturated sampling technique. The number of samples studied was 33 respondents. The analysis used includes percentage calculations, normality tests, correlation coefficient tests, significance tests, and determination coefficient tests. Based on the results of the study, it is known that the Supervision in the Sumedang Regency Social Service is in the very good criteria with analysis results reaching 85%. Then for Effectiveness in the Sumedang Regency Social Service, it is in the very good criteria with analysis results reaching 85%. From the correlation analysis, a correlation value of 0.847 was obtained, indicating a positive and significant relationship between Supervision and Effectiveness in the Sumedang Regency Social Service. From the results of the significance test, a t-count value was obtained which was greater than the t table, namely 8.871> 2.039. From the results of the determination coefficient analysis, it is known that the Supervision variable has an influence on Effectiveness of 71.8% while the remaining 28.2% is influenced by other factors not discussed in this study.